2018
DOI: 10.1055/a-0759-1629
|View full text |Cite
|
Sign up to set email alerts
|

Reprocessing of flexible endoscopes and endoscopic accessories used in gastrointestinal endoscopy: Position Statement of the European Society of Gastrointestinal Endoscopy (ESGE) and European Society of Gastroenterology Nurses and Associates (ESGENA) – Update 2018

Abstract: This Position Statement from the European Society of Gastrointestinal Endoscopy (ESGE) and the European Society of Gastroenterology Nurses and Associates (ESGENA) sets standards for the reprocessing of flexible endoscopes and endoscopic devices used in gastroenterology. An expert working group of gastroenterologists, endoscopy nurses, chemists, microbiologists, and industry representatives provides updated recommendations on all aspects of reprocessing in order to maintain hygiene and infection control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
199
0
68

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(274 citation statements)
references
References 76 publications
0
199
0
68
Order By: Relevance
“…Scopes and accessories should be reprocessed per existing guidelines 52,53 . The majority of gastrointestinal endoscopes are semi‐critical devices that require cleaning and disinfection with agents that have bactericidal, fungicidal, mycobactericidal, and viricidal activity 53 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scopes and accessories should be reprocessed per existing guidelines 52,53 . The majority of gastrointestinal endoscopes are semi‐critical devices that require cleaning and disinfection with agents that have bactericidal, fungicidal, mycobactericidal, and viricidal activity 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Scopes and accessories should be reprocessed per existing guidelines 52,53 . The majority of gastrointestinal endoscopes are semi‐critical devices that require cleaning and disinfection with agents that have bactericidal, fungicidal, mycobactericidal, and viricidal activity 53 . Evidence from a prior study after the severe acute respiratory syndrome outbreak has shown that SARS‐CoV‐1 was readily inactivated by all disinfectants tested (four varieties of hand rubs, three surface disinfectants, and a glutaraldehyde‐based medical instrument disinfectant, 54 suggesting that current reprocessing protocols and high‐level disinfectants are adequate 55 .…”
Section: Methodsmentioning
confidence: 99%
“…Все эндоскопы и эндоскопические инструменты многоразового использования должны обрабатываться в соответствии с установленными стандартами [20,21]. Для обработки используются сертифицированные средства, обладающие бактерицидным, микобактерицидным, фунгицидным, а также вирулицидным действием (против сложных вирусов с липопротеиновой оболочкой и простых вирусов без оболочки).…”
Section: дезинфекция эндоскопического оборудования и инструментовunclassified
“…All national and international societies recommended the rational use of personal protective equipment (PPE) during the diagnostic procedures such as disposable gowns, gloves, FFP2 or N95 respirators and surgical masks, and eye protection (goggles or face shield), based on the experience of health care systems in Asia and Europe [1]; endoscopy staff should be protected against infectious material during the endoscopic procedure as well as against direct contact with contaminated equipment or potentially harmful chemicals during the sterilization procedures [7]. Furthermore, removal of PPE is a high-risk task and great care must be taken not to contaminate self or others during this process [1].…”
mentioning
confidence: 99%